Implementing community care (Buckingham : Open University Press, 1994)
This book is divided into three parts: The policy context; Staff and users; Models of care.
Keywords: Great Britain; Handicapped; Handicapped -- Care -- Great Britain; Handicapped -- Deinstitutionalization -- Great Britain